Strategic Implementation of Big Data Automation for Wastage Management Reporting Using Analytical Hierarchy Process in The Tobacco Industry - Ilham Guspuji Maulana; Yos Sunitiyoso (PT Mattawang Mediatama Solution, 2024)
In today's data-driven era, big data automation is crucial, often referred to as